Evaluation of confirmatory data following the Article 12 MRL review and modification of the existing maximum residue levels for azoxystrobin. (18th August 2020) - ,; Anastassiadou, Maria; Bernasconi, Giovanni; Brancato, Alba; Carrasco Cabrera, Luis; Ferreira, Lucien; Greco, Luna; Jarrah, Samira; Kazocina, Aija; Leuschner, Renata; Magrans, Jose Oriol; Miron, Ileana; et al.
Abstract: The applicant Syngenta submitted a request to the competent national authority in the United Kingdom to evaluate the confirmatory data that were identified for azoxystrobin in the framework of the MRL review under Article 12 of Regulation (EC) No 396/2005 as not available, and to consider new good agricultural practices (GAPs) for lettuces and other salad plants. To address the data gaps, new residue trials performed on open leaf varieties of lettuce supporting adjusted indoor, northern and southern GAPs, an assessment of the genotoxicity of the livestock metabolites L1, L4 and L9 and an assessment of the human dietary exposure to the livestock metabolites L1, L4 and L9 were submitted. The data gaps were considered partially addressed. The new information provided may require a revision (lowering) of the existing MRLs for lettuce and other salad plants and further risk management consideration for MRLs in animal commodities.